Coconut Oil as a Novel Approach to Managing Radiation-Induced Xerostomia: A Primary Feasibility Study. (1st September 2020) - Quimby, Alexandra E.; Hogan, Debora; Khalil, Diana; Hearn, Matthew; Nault, Colette; Johnson-Obaseki, Stephanie
Abstract : Background . Xerostomia is a common complication following radiation therapy for head and neck cancer (HNC), for which there is no single, universally accepted therapy. Coconut oil has been anecdotally suggested to provide relief for this complication. This study sought to examine the feasibility and effectiveness of coconut oil as a therapy for radiation-induced xerostomia. Methods . A feasibility study was performed among 30 patients with xerostomia subsequent to radiation for HNC. Coconut oil samples were provided along with a protocol for use over a 2-week period and the option to continue if they found it beneficial. Patients were also instructed to keep diaries to document their patterns of use. The Xerostomia-related Quality of Life Scale (XeQOLS) was administered at baseline and 3-month follow-up. Descriptive methods were used to summarize patterns of coconut oil use and paired t -tests were used to assess changes in XeQOLS scores over time. Results . The mean total duration of coconut oil use during the study period was 16 days (1–71). The average number of uses per day was 3 (1–5), with an average amount per use of 5 mL (1.2–8.5). Twelve patients (41.4%) continued coconut oil use beyond the advised period. There was no statistically significant difference in XeQOLS scores pre- and post-treatment. There were no adverse events during the study period. Conclusions . The use of coconut oil as a treatment strategy for xerostomia post-HNC radiation is feasible, inexpensive, and safe. This study demonstrates that there may be a group of HNC patients that benefit from its use.